2017
DOI: 10.1021/acs.biochem.7b00890
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Dynamics of the Oxidized Y48H Variant of Human Cytochrome c Increases Its Peroxidatic Activity

Abstract: Proteins performing multiple biochemical functions are called "moonlighting proteins" or extreme multifunctional (EMF) proteins. Mitochondrial cytochrome c is an EMF protein that binds multiple partner proteins to act as a signaling molecule, transfers electrons in the respiratory chain, and acts as a peroxidase in apoptosis. Mutations in the cytochrome c gene lead to the disease thrombocytopenia, which is accompanied by enhanced apoptotic activity. The Y48H variant arises from one such mutation and is found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
103
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(121 citation statements)
references
References 84 publications
15
103
2
Order By: Relevance
“…In contrast, recent studies of azide binding to human WT cyt c have revealed a slower Met80 dissociation process with k 1 = 5.77±1.5 s −1 , 67 which is accelerated by mutations in the Ω-loop C (residues 40–57) of the protein. 68 …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, recent studies of azide binding to human WT cyt c have revealed a slower Met80 dissociation process with k 1 = 5.77±1.5 s −1 , 67 which is accelerated by mutations in the Ω-loop C (residues 40–57) of the protein. 68 …”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, all the tested alterations of Ser47 resulted in an inefficient caspase activator . Moreover, the G41S and Y48H mutants, which are responsible for the onset of the thrombocytopenia‐4 disease, showed enhanced caspase‐3 activation activity .…”
Section: Cytochrome C In the Cytoplasm: Established And New Targetsmentioning
confidence: 96%
“…The replacement of Tyr48 by the positively charged histidine caused several functional changes, including reduced oxygen consumption rate and increased apoptosis (63). A recent study on the Tyr48His variant showed that the pentacoordinated form of Cytc, which promotes cardiolipin peroxidase activity, is more prevalent in the mutant, further supporting the increased apoptotic activity (71). Molecular dynamics simulations concluded that both Gly41Ser and Tyr48His mutations result in a less stable and more open protein structure, which would promote cardiolipin peroxidase activity (72).…”
Section: Tyr48 Phosphorylationmentioning
confidence: 98%